The impact of early monitored management on survival in hospitalized adult Ugandan patients with severe sepsis: a prospective intervention study - Jacob, Shevin T; Banura, Patrick; Baeten, Jared M.; Moore, Christopher C.; Meya, David; Nakiyingi, Lydia; Burke, Rebecca; Horton, Cheryl Lynn; Iga, Boaz; Mayanja-Kizza, Harriet; for the Promoting Resource-Limited Interventions for Sepsis Management in Uganda (PRISM-U) Study Group The impact of early monitored management on survival in hospitalized adult Ugandan patients with severe sepsis: a prospective intervention study (Critical care medicine, 2012)
In sub-Saharan Africa, sepsis is an important cause of mortality but optimal sepsis management including fluid resuscitation, early antibiotic administration and patient monitoring is limited by a lack of supplies and skilled health workers.To evaluate whether early, monitored sepsis management provided by a study medical officer can improve survival among patients with severe sepsis admitted to two public hospitals in Uganda.A prospective before and after study of an intervention cohort (n=426) with severe sepsis receiving early, monitored sepsis management compared to an observation cohort (n=245) of similarly ill patients with severe sepsis receiving standard management after admission to the medical wards of two Ugandan hospitals.Early sepsis management provided by a dedicated study medical officer comprised of fluid resuscitation, early antibiotics and regular monitoring in the first 6 hours of hospitalization.Kaplan-Meier survival and unadjusted and adjusted Cox proportional hazards analysis were used to compare the effect of early, monitored sepsis management on 30-day mortality between the intervention cohort (enrolled May 2008 to May 2009) and observation cohort (enrolled July 2006 to November 2006).The majority (86%) of patients in both cohorts were HIV-infected. Median fluid volume provided in the first 6 hours of hospitalization was higher in intervention than observation cohort patients (3000 vs. 500 mL, p<0.001) and a greater proportion of intervention cohort patients received antibacterial therapy in less than one hour (67% vs 30.4%, p<0.001). Mortality at 30 days was significantly lower in the intervention cohort compared to the observation cohort (33.0% vs 45.7%, log-rank p=0.005). After adjustment for potential confounders, the hazard of 30-day mortality was 26% less in the intervention cohort compared to the observation cohort (adjusted HR=0.74, 95% CI=0.55–0.98). Mortality among the 13% of intervention patients who developed signs of respiratory distress was associated with baseline illness severity rather than fluid volume administered.Early, monitored management of severely septic patients in Uganda improves survival and is feasible and safe even in a busy public referral hospital.
Keywords: Sepsis, Management Bundle, Fluid Therapy, Uganda, Africa, Mortality, Pulmonary Edema